Skrining Resep Polifarmasi Secara Klinis Pada Pasien Diabetes Melitus Tipe II Di Rumah Sakit Advent - Nur Afni Br. Ritonga; Novitaria Br. Sembiring; Elfia Neswita; Razoki (Journal of Pharmaceutical and Sciences, 2023)
A few examples of clinical criteria include precise indications, duplication therapy, allergies, unexpected drug reactions (ROTD), contraindications, and drug interactions. Staff employees in the pharmaceutical industry screen prescriptions to prevent the occurrence (Medication errors). According to Hindratni et al. (2017), treatment errors occur when medical professionals handle patients while giving them potentially harmful medications. Research Objectives to comprehend the frequency and seriousness of drug interactions that arise when diabetes mellitus drugs are administered in Adventist hospitals. This study uses descriptive research methods and retrospective research designs, which means it looks at the material already gathered and generated from October and December 2022 recipe dataThe 500 or so prescriptions that IFRS Adventist Medan received between October and December 2022 are where the recipes were collected. Five hundred tablets were used as a sample, and 131 met the criteria for inclusion in the clinical screening of polypharmacy prescriptions in patients with type II diabetes mellitus at Adventist hospitals. 100 percent of the 131 prescriptions were correct regarding indications, drug doses, instructions, methods, and duration of use. Three different drugs, or 25% of all medications, have interactions. The drugs they interacted with were found in 4 prescriptions or 72%. The number of pills (65.21%) containing the drugs they interacted with was 5. Six medicines (60.71%) included medications that interacted with one another. There were seven prescriptions (52.94%) that had interactions with drugs.